Plant tolerance to individual and concurrent stresses - Senthil-Kumar, Muthappa (Springer, 2017)
This book focuses on multiple plant stresses and the molecular basis of adaptation, addressing the molecular mechanism and adaptation for both abiotic and biotic stresses. Ensuring the yield of crop plants grown under multiple individual and/or combined stresses is essential to sustaining productivity. In this regard, the development of broad-spectrum stress-tolerant plants is important. However, to date information has largely been compiled only on the individual stress tolerance mechanisms, and the mechanisms behind plants tolerance to two or more individual or simultaneous stresses are not fully understood. Especially combinatorial stress, a new stress altogether, has only recently been made the object of systematic study. Now several research groups around the world have begun exploring the concurrent stress tolerance mechanisms under both biotic and abiotic stress combinations. This book presents contributions from various experts, highlighting the findings of their multiple individual and concurrent stress tolerance dissection studies.
Keywords: Plants -- Effect of stress on.; elektronické knihy; electronic books